A little princess - Burnett, Frances Hodgson (b, 2016)
Sara Crewe, a pupil at Miss Minchin's London school, is left in poverty when her father dies but is later rescued by a mysterious benefactor.
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Orphans -- Fiction